The Potential of the Blue Economy : Increasing Long-term Benefits of the Sustainable Use of Marine Resources for Small Island Developing States and Coastal Least Developed Countries - World Bank; United Nations Department of Economic and Social Affairs (World Bank, Washington, DC, 2017)
This report was drafted by a working group of United Nations entities, the World Bank, and other stakeholders to suggest a common understanding of the blue economy; to highlight the importance of such an approach, particularly for small island developing states and coastal least developed countries; to identify some of the key challenges its adoption poses; and to suggest some broad next steps that are called for in order to ensure its implementation. Although the term “blue economy” has been used in different ways, it is understood here as comprising the range of economic sectors and related policies that together determine whether the use of oceanic resources is sustainable. An important challenge of the blue economy is thus to understand and better manage the many aspects of oceanic sustainability, ranging from sustainable fisheries to ecosystem health to pollution. A second significant issue is the realization that the sustainable management of ocean resources requires collaboration across nation-states and across the public-private sectors, and on a scale that has not been previously achieved. This realization underscores the challenge facing the Small Island Developing States (SIDS) and Least Developed Countries (LDCs) as they turn to better managing their blue economies.